Mix Design: Effect of Mixing Constituents towards Palm Oil Clinker Lightweight Aggregate Concrete - Nur Azzimah, Zamri; Khairunisa, Muthusamy; Kusbiantoro, Andri; Nasly, Mohamed Ali (Universiti Malaysia Pahang, 2016)
Use of waste materials as substitutes in the production of concrete that improve some important properties of the hardened lightweight aggregate concrete such as mechanical and durability properties are grabbing the researchers’ attention nowadays. This is due to lightweight aggregate concrete low density that resulted in reduction of dead load, faster building rates in construction and also lower transportation and handling costs compared with normal concrete. Palm oil clinker, one of the by-product produced abundantly from palm oil industry is dumped as waste without any profitable value which caused negative effects to the environment. At the same time, large quantities of coarse aggregate are produced from quarries around and has disastrous environmental consequences. To produce coarse aggregate for concrete, mountains had to be ‘slaughtered’ in which intensifies erosion problem. Due to this activity, natural resources is becoming a deficient commodity and hence exploring replacement to it has become imminent. Thus, this research was conducted to investigate the best mix proportion to produce palm oil clinker lightweight aggregate concrete. In this research, a by-product from palm oil industry called as palm oil clinker was used as conventional aggregate replacement in concrete mixture. The result shows that it is possible to produce high strength lightweight aggregate clinker with strength of 75 MPa with suitable mix proportion. As a conclusion, recycling this palm oil waste not only helps reduce the huge amount of global palm oil waste sent for disposal, but also helps conserve natural resources by replacing the need for virgin materials.